2005
DOI: 10.1093/humrep/dei295
|View full text |Cite
|
Sign up to set email alerts
|

Contractile reactivity of human myometrium in isolated non-pregnant uteri

Abstract: Continuous E2 treatment, with the addition of OT for the last 3 h of the 27 h perfusion period, led to the most pronounced uterotonic effects in the presented experimental condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
22
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 41 publications
4
22
1
5
Order By: Relevance
“…The results presented here are in accordance with those first described by Bulletti et al [21] and those reported by Richter et al [23] in extracorporeal perfused human uteri. Both groups of authors described a characteristic increase in IUP after perfusion with estrogens.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The results presented here are in accordance with those first described by Bulletti et al [21] and those reported by Richter et al [23] in extracorporeal perfused human uteri. Both groups of authors described a characteristic increase in IUP after perfusion with estrogens.…”
Section: Discussionsupporting
confidence: 94%
“…Stimulation with highdose of 17β-estradiol increased myometrial OTR density, with maximum levels found in the uterine fundus [11]. In particular, pretreatment with 17β-estradiol before oxytocin stimulation resulted in a larger and more prolonged uterine response to oxytocin application [23], while progesterone stimulation directly resulted in a reduction of both the frequency and duration of uterine contractility, as reported by Bulletti et al [21].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Previous investigations have validated the feasibility of this perfusion model of isolated uteri for various purposes (25)(26)(27)(28)(29)(30)(31). This perfusion model is able to keep the uterus in a functional condition and is suitable for the study of physiologic questions (32)(33)(34).…”
mentioning
confidence: 84%